Development of a multiplex PCR system for the simultaneous detection of white spot syndrome virus and hepatopancreatic parvovirus infection. Issue 6 (16th October 2012) - Jeeva, Subbiah; Kim, Nam‐Il; Jang, In‐Kwon; Choi, Tae‐Jin
Abstract A multiplex PCR kit for simultaneous detection of white spot syndrome virus (WSSV) and hepatopancreatic parvovirus (HPV) was developed and field testing was conducted. A 604‐bp target sequence was selected from the vp28 gene of WSSV. A primer set was developed to amplify a 338‐bp DNA fragment at the junction of the NS2 and NS1 protein genes of HPV after alignment of eight sequences from different strains. Another internal positive control primer set produced a 139‐bp PCR fragment from the β‐actin gene by alignment of this gene from Litopenaeus vannamei, Fenneropenaeus chinensis and Penaeus monodon. The detection limits, tested using purified plasmids, for WSSV and HPV were 21.4 and 19.0 copies respectively. The optimum ratio for HPV, WSSV and β‐actin was 3:1:1, with an optimum annealing temperature of 57°C. Field test of the multiplex PCR with 170 L. vannamei individuals from 17 aquaculture farms showed 41.8% coinfection with WSSV and HPV, and 40.0% and 3.5% single infection with WSSV and HPV respectively. No virus‐free shrimp farm was found. Ten wild catch F. chinensis individuals showed 60% coinfection, and 40% were infected with HPV.